Bench to bedside: A role for erythropoietin in sepsis. - Walden, A; Young, J; Sharples, E (2010)
Sepsis is the systemic inflammatory response to infection and can result in multiple organ dysfunction syndrome with associated high mortality, morbidity and health costs. Erythropoietin is a well-established treatment for the anaemia of renal failure due to its anti-apoptotic effects on red blood cells and their precursors. The extra-haemopoietic actions of erythropoietin include vasopressor, anti-apoptotic, cytoprotective and immunomodulating actions, all of which could prove beneficial in sepsis. Attenuation of organ dysfunction has been shown in several animal models and its vasopressor effects have been well characterised in laboratory and clinical settings. Clinical trials of erythropoietin in single organ disorders have suggested promising cytoprotective effects, and while no randomised trials have been performed in patients with sepsis, good quality data exist from studies on anaemia in critically ill patients, giving useful information of its pharmacokinetics and potential for harm. An observational cohort study examining the microvascular effects of erythropoietin is underway and the evidence would support further phase II and III clinical trials examining this molecule as an adjunctive treatment in sepsis.